Smart Home System Design Using NodeMCU Based on the Internet of Things (IoT) - Irwan, Irwan; Kartini, Siti Agus; Sabila, Puji Chairu (Bahasa Indonesia, 2024)
The Internet of Things is automation in all fields of activities and aspects of life through technology, electronic connections or digital connections across devices and fields. IoT is the latest technology trend that continues to develop and provides the latest innovations in various sectors, one of which is controlling electrical devices remotely through the internet of things. This system can help make it easier to control without the need to do it manually. With many rooms in a building, it can shorten the time so that you don't have to check the rooms one by one again. The system is implemented using NodeMCU, relay, Apple HomeKit, and Siri (voice) as the system interface. The system takes an average of 0.4 - 3.3 seconds to respond to commands from Apple HomeKit and Siri via a Wifi connection with a distance of 1-10 meters based on monitoring results, and the electrical power control and monitoring system can function properly. The length of the system's response time is not affected by distance, but rather by the network. This system accessed using Wifi is the most effective alternative compared to using longer SMS and Bluetooth with a shorter range. With the implementation of IoT technology, humans can be more effective, efficient, economical, and easy in monitoring and controlling electrical devices at home.